Identification and Characterization of the Stability of Hydrophobic Cyclolinopeptides From Flaxseed Oil - Fojnica, Adnan; Leis, Hans-Jörg; Murkovic, Michael (Frontiers in Nutrition, 2022)
Flaxseed (linseed) is a cultivar of the spring flowering annual plant flax (Linum usitatissimum) from the Linaceae family. Derivatives of this plant are widely used as food and as health products. In recent years, cyclic peptides isolated from flaxseed and flaxseed oil, better known as cyclolinopeptides (CLPs), have attracted the attention of the scientific community due to their role in the inhibition of osteoclast differentiation or their antimalarial, immunosuppressive, and antitumour activities, as well as their prospects in nanotechnology and in the biomedical sector. This study describes the detection, identification, and measurement of CLPs in samples obtained from nine different flaxseed oil manufacturers. For the first time, Q Exactive Hybrid Quadrupole-Orbitrap Mass Spectrometry was used for CLP identification together with RP-HPLC. The routine analyses were performed using RP chromatography measuring the absorption spectra and fluorescence detection for identifying tryptophan-containing peptides using the native fluorescence of tryptophan. In addition, existing protocols used for CLP extraction were optimized and improved in a fast and cost-efficient way. For the first time, 12 CLPs were separated using methanol/water as the eluent with RP-HPLC. Finally, the stability and degradation of individual CLPs in the respective flaxseed oil were examined over a period of 60 days at different temperatures. The higher temperature was chosen since this might reflect the cooking practices, as flaxseed oil is not used for high temperature cooking. Using HPLC–MS, 15 CLPs were identified in total in the different flaxseed oils. The characterization of the peptides via HPLC–MS highlighted two types of CLPs profiles with a substantial variation in the concentration and composition of CLPs per manufacturer, probably related to the plant cultivar. Among the observed CLPs, CLP-O, CLP-N, and CLP-B were the least stable, while CLP-C and CLP-A were the most stable peptides. However, it is important to highlight a gradual degradation of most of the examined CLPs over time, even at room temperature.